2005
DOI: 10.1002/marc.200500219
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chain Architecture of In Situ Formed Copolymers on Interfacial Morphology of Reactive Polymer Blends

Abstract: Summary: The effect of chain architecture of in situ formed copolymers on the interfacial morphology of reactive polymer blends was investigated. We found that the chain architectures of copolymers at the interface significantly affected the reaction and interface roughness. Although the amount of in situ formed Y‐shaped graft copolymers was smaller than that for diblock copolymers, the interface area generated by the former was larger than that generated by the latter.Cross‐sectional TEM images for the mid‐sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
(37 reference statements)
0
25
0
Order By: Relevance
“…This might be due to the chain architecture of in situ formed PMMA‐ g ‐PS copolymers. We previously reported that the interfacial curvature can be easily stabilized, and small‐sized microemulsions are observed when the head (the PMMA phase in this study) of Y‐shaped graft copolymer is located at the outer side of the curvature 23. On the other hand, once microemulsions are formed in the PS phase, the head of Y‐shaped graft copolymers should be located inside of the microemulsions, which makes microemulsions larger.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…This might be due to the chain architecture of in situ formed PMMA‐ g ‐PS copolymers. We previously reported that the interfacial curvature can be easily stabilized, and small‐sized microemulsions are observed when the head (the PMMA phase in this study) of Y‐shaped graft copolymer is located at the outer side of the curvature 23. On the other hand, once microemulsions are formed in the PS phase, the head of Y‐shaped graft copolymers should be located inside of the microemulsions, which makes microemulsions larger.…”
Section: Resultsmentioning
confidence: 59%
“…This is because the reaction can proceed further with annealing time without shear, which generates sufficient amounts of graft copolymers near the interface to reduce the interfacial tension of two polymers. However, microemulsions are seen in both PMMA and PS phases, which is distinctly different from the situation where microemulsions are seen in only the PMMA phase when the reactive bilayer is simply annealed (or even parallel shearing at smaller γ 0 and ω ) at 180 °C for 24 h without experiencing perpendicular shearing 23, 30. Furthermore, the microemulsions observed in the PMMA phase look smaller than that observed in the PS phase.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Recently, many studies have focused on investigating the effect of reaction kinetics on the interfacial morphology of reactive bilayer system using transmission electron microscopy (TEM), atomic force microscopy (AFM), forward recoil spectrometry (FRES), and dynamic secondary ion mass spectrometry [12][13][14][15][16][17][18][19][20][21][22][23][24]. It should be noted that the interfacial morphology of reactive bilayer system depends on the reaction kinetics of two reactive polymers, the position of the functional group in a reactive polymer chain, and the molecular weight of the polymers.…”
Section: Introductionmentioning
confidence: 99%